PROBLEMS OF CONFORMITY OF THE RECORDS INTEGRITY WITH THE REQUIREMENTS OF GOOD MANUFACTURING PRACTICE. REPORT 1. ACTUALITY OF THE RECORDS INTEGRITY CONSERVATION - I. A. Osmolovskaya; O. V. Zarochinskaya; M. O. Emelianov; D. V. Somov (Разработка и регистрация лекарственных средств)
Integrity of records or data integrity is the most «hot» requirement when assessing documentation systems for compliance with Good Manufacturing Practice (GMP). It's in the center of focus of attention during inspections of pharmaceutical companies. This article is the first of a series of articles devoted to this topic. In it explains the reasons for the importance of preserving the integrity of records and provides examples of identified deviations.